Psychological-Pedagogical And Methodological Bases Of The Development Of Educational Content Of The Data Sheet (Eurasian Scientific Herald, 2022)
In this article, the psychological-pedagogical and methodological basis of the development of the educational content of the data construction is discussed. In addition, the introduction of the concept of progressive cognitive education is aimed at increasing the effective side of education, improving the functions of educational and cognitive process management.